Fruquintinib Enhances the Antitumor Immune Responses of Anti-Programmed Death Receptor-1 in Colorectal Cancer - Li, Qingli; Cheng, Xiaojiao; Zhou, Cong; Tang, Yao; Li, Fuli; Zhang, Baiwen; Huang, Tinglei; Wang, Jianzheng; Tu, Shuiping (Frontiers in Oncology, 2022)
Background: Programmed death receptor-1 (PD-1) blockade shows little benefit in patients with microsatellite-stable colorectal cancer (MSS-CRC). Fruquintinib is a China-made anti-angiogenic drug which is applied for the third line therapy in mCRC. This study investigates the effect of the combination of fruquintinib and PD-1 blockade on MSS-CRC and its relative mechanisms. Methods: The tumor xenograft mouse models that represent MSS and microsatellite instability (MSI) CRC were established using murine CT26 and MC38 colon cancer cells, respectively, to assess the treatment efficacy. The percentages of immune cells were detected in the peripheral blood, spleen and tumor tissues in the tumor-bearing mice by flow cytometry analysis. Angiogenesis in tumor tissues was detected by immunofluorescence. The safety of drug treatment was evaluated by histopathology analysis in murine main organs. The efficacy of the combination of fruquintinib and sintilimab were verified in the treatment of MSS-CRC patients. Results: Our results showed that the combination of fruquintinib and sintilimab exhibited the strongest inhibition of tumor growth and achieved the longest survival time in mice bearing MC38 or CT26 xenograft tumors, compared to fruquintinib and sintilimab alone. Mechanistically, the combination of fruquintinib and sintilimab reduced angiogenesis, reprogramed the vascular structure, enhanced the infiltration of CD8+T cells, CD8+TNFα+T cells and CD8+IFNγ+T cells and reduced the ratios of MDSCs and macrophages in mice. There was no obvious toxicity observed in the main organs of the tumor-bearing mice with the combined treatment. Moreover, the treatment using the combination of fruquintinib and sintilimab achieved effective response in five patients with refractory advanced MSS CRC. Conclusion: Our results show that the combination of fruquintinib and sintilimab synergistically inhibits CRC growth by altering tumor immune microenvironment. This study provides the rational for using the combination of fruquintinib and anti-PD-1 antibody for the treatment of advanced CRC.